2016
DOI: 10.1161/jaha.116.003540
|View full text |Cite
|
Sign up to set email alerts
|

Race‐Specific Predictors of Mortality in Intracerebral Hemorrhage: Differential Impacts of Intraventricular Hemorrhage and Age Among Blacks and Whites

Abstract: BackgroundIntracerebral hemorrhage (ICH) carries high risk for short‐term mortality. We sought to identify race‐specific predictors of mortality in ICH patients.Methods and ResultsWe used 2 databases, the Johns Hopkins clinical stroke database and the Nationwide Inpatient Sample (NIS). We included 226 patients with the primary diagnosis of spontaneous ICH from our stroke database between 2010 and 2013; in the NIS, 42 077 patients met inclusion criteria. Logistic regression was used to assess differences in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Smoking is considered as an important predictor of substantial hematoma expansion (SHE), short-and long-term mortality, and poor outcome in sICH patients. [86][87][88] As mentioned previously, hematoma expansion occurs in the majority of sICH patients following ictus. The risk of post-ictus hematoma expansion is higher in tobacco-using sICH patients.…”
Section: Outcomes Following Sich In Tobacco Usersmentioning
confidence: 71%
See 2 more Smart Citations
“…Smoking is considered as an important predictor of substantial hematoma expansion (SHE), short-and long-term mortality, and poor outcome in sICH patients. [86][87][88] As mentioned previously, hematoma expansion occurs in the majority of sICH patients following ictus. The risk of post-ictus hematoma expansion is higher in tobacco-using sICH patients.…”
Section: Outcomes Following Sich In Tobacco Usersmentioning
confidence: 71%
“…Besides increasing the risk of sICH, earlier clinical studies also established that tobacco use also worsens outcomes following sICH ( Figure 1 ). Smoking is considered as an important predictor of substantial hematoma expansion (SHE), short- and long-term mortality, and poor outcome in sICH patients [ 86 - 88 ]. As mentioned previously, hematoma expansion occurs in the majority of sICH patients following ictus.…”
Section: Outcomes Following Sich In Tobacco Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…The third is the uniform diagnosis of ICH and the availability of variables including components of the ICH score and FUNC score to control for clinical severity and comorbid conditions that impact CMO decisions. 2830 Furthermore, demographic information including education level and insurance status were available to evaluate other influences on CMO decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Race/population-specific influences of smoking on ICH incidence have also been reported. A study by Faigle et al (2016) showed that smoking was one of the predictors of mortality in white populations, but not black populations, of ICH patients. In addition, meta-analyses of the risk factors for ICH and ischemic stroke suggest that smoking is a risk factor more frequent in ischemic stroke in white population but not in Chinese population (Tsai et al 2016).…”
Section: Nicotine Smoking and Stroke: Potential Associationsmentioning
confidence: 99%